PELATIHAN SINGKAT TENTANG PENGETAHUAN DAN KETERAMPILAN DALAM DETEKSI DINI PERKEMBANGAN ANAK BALITA - Husni, Husni (JURNAL MEDIA KESEHATAN, 2018)
The incidence of child development deviation in Indonesia reached 13% -18%. About 16% of children under five years got neurodevelopmental and brain disorders from mild to severe. This study aimed to determine the effect of brief training by using Pre- Screening Questionnaire Development (KPSP) to improve the knowledge and skills of parents in detection of child development. This study was quasi experimental with prepost test only. The population in this study were the parents / guardians of children at kinder garten of Baitul Izzah and Al Hasanah Bengkulu City. Samples were parents who have never participated in training and at least high school education. Number of samples 56 (28 intervention and 28 control) taken with concecutive sampling techniques. Data collection were using questionnaire for knowledge and checklist for skills. Statistical test independent t-test at the ? 5% (one tail). The results showed the average age was 33 years, the average income was 2.3 million per month, more mothers working and have higher education. There were the difference in knowledge after being given brief training of 27.5 (p value = 0.000) and the difference in ability between the intervention and control groups (p value = 0.000). Effectiveness of brief training to increase the knowledge of 35%. factor affecting the mother's knowledge was the age (p 0.001; OR: 2.12). We concluded that parents are expected to apply the child development detection according to ability at home and it is needed training for other parents.